Exergy Assessment and Thermo-Economic Analysis of Hybrid Solar Systems with Seasonal Storage and Heat Pump Coupling in the Social Housing Sector in Zaragoza - Amaya Martínez-Gracia (Energies, 2021)
A real case study of an energy system based on a Solar Assisted Heat Pump (SAHP) fed by hybrid photovoltaic-thermal solar panels (PVT) and seasonal storage (SS) is presented in this paper. Exergy and exergy cost analyses are proposed as complementary methods for the assessment and better understanding of the efficiency of this cogeneration solar configuration. The system performance takes advantage of storage heat in summer, when the solar resource is high in Spain, and is then later consumed during the cold winter (heating season). The building is devoted to social housing, and it is currently under construction. The assessment is based on simulations developed using TRNSYS, a dynamic simulation software for energy systems. Results show that the unit exergy cost of the solar field is around 6. The cost of the seasonal storage is higher, about 13, and its formation is affected both by its own irreversibility and by the irreversibility of the PVT solar field. The cost of the heat delivered by the heat pump is around 15, being affected by all the upstream units and even by the grid. Besides, the analysis points out strategies for improving the system efficiency, such as increasing the size of the storage tank or improving the control strategy of the boiler.